Active learning of programming in engineering classes: an action reseach study (Research, Society and Development, 2019)
Engineering is an area of knowledge in which calculations are needed. The computation is present in the daily life of the engineer supporting their simulations, calculations and research. The objective of this article is to present an experience report in programming teaching in an engineering course in which there was previously difficulty learning and engaging. It was decided to work with active methodology and practices in the Zone of Proximal Development (ZPZ) predicted in the vygostikyana theory. An action-research work was done in classes of a civil engineering course in which the actors decided to change the form of programming teaching that started to involve the parallel learning of: system analysis, logic, algorithms, programming and visualization of results. There was a significant improvement in the approval rates, there was an improvement in the engagement of students who worked together to exchange opinions and support peers through peer work. It is believed that work in the ZPD associated with collaborative work and parallel learning has encouraged engagement and increased interest in programming and computing.